Foretelling the end of capitalism intellectual misadventures since Karl Marx - Boldizzoni, Francesco, 1979- (Harvard University Press, 2020)
"Prophecies about the end of capitalism are as old as capitalism. None of them, so far, has come true. Yet we keep looking into the crystal ball in search of harbingers of doom. Francesco Boldizzoni gets to the root of the very human need to imagine a better world and uncovers the mechanisms by which the same forecasting mistakes are made over and over again. He offers a compelling solution to the puzzle of what is capitalism and why it seems able to survive all sorts of shocks. The global crisis that developed countries faced at the beginning of the twenty-first century has undermined faith in the capitalist market economy bringing once again to the forefront questions about its long-term prospects. Is capitalism on its way out? If not, what should be expected from future crises? Will society be able and willing to bear the social and environmental costs of creative destruction and relentless financialization? These and other questions have lain at the heart of political economy since the age of Karl Marx. Foretelling the End of Capitalism takes us on a journey through two centuries of unfulfilled prophecies to challenge the belief in an immutable destiny"--